1989
DOI: 10.1002/mrc.1260270102
|View full text |Cite
|
Sign up to set email alerts
|

Triazoles. XIV—15N NMR study of substituted 5‐amino‐1,2,4‐triazoles

Abstract: 15N NMR chemical shifts were measured for a series of substituted 5‐amino‐1,2,4‐triazoles. The assignment of isomeric structures agrees with earlier results obtained with the use of proton‐coupled 13C NMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
2
14
0
1
Order By: Relevance
“…The chemical shift of the NH 2 groups appearing at δ = 6.1, 6.0, 6.0 and 6.05 ppm, respectively, even not excluding the 4H tautomeric structure points rather to their 1H dominant tautomeric structure in agreement with the previous results obtained with the 5-amino-3-alkylthio-1,2,4-triazoles [21] (Scheme 6) and corroborated also by 15 N-nmr [22]. respectively.…”
Section: Sep-oct 2003 821supporting
confidence: 91%
“…The chemical shift of the NH 2 groups appearing at δ = 6.1, 6.0, 6.0 and 6.05 ppm, respectively, even not excluding the 4H tautomeric structure points rather to their 1H dominant tautomeric structure in agreement with the previous results obtained with the 5-amino-3-alkylthio-1,2,4-triazoles [21] (Scheme 6) and corroborated also by 15 N-nmr [22]. respectively.…”
Section: Sep-oct 2003 821supporting
confidence: 91%
“…A preparative proof for structure 6 of the products obtained showed that S-alkylation reactions of 6 give products of type 1 identical with those obtained previously [2] by the ring closure of the S-alkyl triazoles (4) with the corresponding ortho-acyl phenylacetones (2) (Scheme 3, Tables II and IIa).…”
Section: Nov-dec 2003 1041supporting
confidence: 76%
“…To corroborate the above idea a 6b type N-benzyl derivative 9 was synthesised as a model compound by structure proving synthesis starting from the corresponding 2 (R = 4-chlorophenyl, R 1 , R 2 = methoxy) and 3-amino-4-benzyl-4,5-dihydro-1H-1,2,4-triazole-5-thione (8) [4] (Scheme 5). The carbon atom 5' of derivative 9 was shifted downfield to 169.1 ppm as compared with those of derivatives 6 appearing at 159.3-162.9 ppm pointing out its 5'thione structure.…”
Section: Nov-dec 2003 1041mentioning
confidence: 99%
See 2 more Smart Citations